Hospital discharge: What are the problems, information needs and objectives of community pharmacists? A mixed method approach - Brühwiler LD; Hersberger KE; Lutters M (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Background: After hospital discharge, community pharmacists are often the first health care professionals the discharged patient encounters. They reconcile and dispense prescribed medicines and provide pharmaceutical care. Compared to the roles of general practitioners, the pharmacists' needs to perform these tasks are not well known. Objective: This study aims to a) Identify community pharmacists' current problems and roles at hospital discharge, b) Assess their information needs, specifically the availability and usefulness of information, and c) Gain insight into pharmacists' objectives and ideas for discharge optimisation. Methods: A focus group was conducted with a sample of six community pharmacists from different Swiss regions. Based on these qualitative results, a nationwide online-questionnaire was sent to 1348 Swiss pharmacies. Results: The focus group participants were concerned about their extensive workload with discharge prescriptions and about gaps in therapy. They emphasised the importance of more extensive information transfer. This applied especially to medication changes, unclear prescriptions, and information about a patient's care. Participants identified treatment continuity as a main objective when it comes to discharge optimisation. There were 194 questionnaires returned (response rate 14.4%). The majority of respondents reported to fulfil their role as defined by the Joint-FIP/WHO Guideline on Good Pharmacy Practice (rather) badly. They reported many unavailable but useful information items, like therapy changes, allergies, specifications for "off-label" medication use or contact information. Information should be delivered in a structured way, but no clear preference for one particular transfer method was found. Pharmacists requested this information in order to improve treatment continuity and patient safety, and to be able to provide better pharmaceutical care services. Conclusion: Surveyed Swiss community pharmacists rarely receive sufficient information along with discharge prescriptions, although it would be needed for medication reconciliation. According to the pharmacist's opinions, appropriate pharmaceutical care is therefore impeded.